Digital Divide in iPusnas Utilization by Students of Universitas Pembangunan Nasional “Veteran” Jakarta - Mohammad Rafatta Umar; Tsalitsa Haura Layyina; Cindy; Andini Nathania Putri; Fatkhuri (ARRUS Journal of Social Sciences and Humanities, 2025)
Internet usage in Indonesia has reached 212 million individuals as of February 2025. This indicates the need for the government to innovate and use technology to implement good governance. One of the problems in Indonesia is the low literacy of the community, and one of the causes is the lack of affordable access to books due to high prices. Through the Indonesian National Library, the Indonesian government has created the iPusnas application, a digital public library. However, technological innovation always faces the challenge of the digital divide. Through this research, the author examines the digital divide in the utilization of iPusnas by students of the National Development University “Veteran” Jakarta (UPNVJ) using digital divide theory. With a qualitative method, the author uses primary data through interviews with UPNVJ students from all faculties to explore the subjective experience of each informant. The result of the research is that most interviewees do not know the application, even though they have sufficient technology to access it. This requires a solution in the form of greater socialization from the application manager to the community through social media or direct socialization.